Application of three-dimensional (3D) reconstruction in the treatment of video-assisted thoracoscopic complex segmentectomy of the lower lung lobe: A retrospective study - Wang, Xinyu; Wang, Qing; Zhang, Xindi; Yin, Hang; Fu, Yujie; Cao, Min; Zhao, Xiaojing (Frontiers in Surgery, 2022)
Background: An increasing number of lung ground-glass nodules (GGNs) have been detected since the popularity of low-dose computer tomography. Three-dimensional (3D) reconstruction technology plays a critical role in lung resection, especially for segmentectomy. In this study, we explore the role of 3D reconstruction in thoracoscopic complex segmentectomy of lower lung lobes. Methods: A total of 97 patients underwent complex segmentectomy of lower lung lobes from January 2021 to March 2022 were retrospectively analyzed. We divided these patients into 3D group (n=42) and routine group (n=55) based on preoperative 3D reconstruction or without. The demographics of patients and GGNs were collected and perioperative outcomes were compared between the two groups. Results: All of the baseline characteristics between groups were comparable (all P>0.05). There was no 30-day postoperative mortality and conversion in the two groups. The operation time of the 3D group was significantly shorter than that of routine group (111.4 ± 20.8 min verse 127.1 ± 32.3 min, P=0.007). The numbers of stapler reload during surgery in the 3D group were less than that in the routine group (9.0 ± 2.2 vs 10.4 ± 2.6, P=0.009). The rate of air leakage on postoperative day 1-3 was lower in the 3D group (11.9% vs 30.9%, P=0.027). In addition, the resection margins of all the patients in the 3D group were adequate while 4 patients in the routine group had inadequate resection margins, although there was not statistically significant (P=0.131). Intraoperative blood loss, postoperative drainage, postoperative hospital stay, pneumonia/atelectasis and hemoptysis were similar between the two groups. Conclusions: For complex segmentectomy of lower lung lobes, 3D reconstruction may shorten the operation time, decrease the numbers of stapler reload, prevent postoperative air leakage and guarantee a safe surgical margin. 3D reconstruction is recommended for complex segmentectomy of lower lung lobes.